Multiecho acquisition of O‐space data. Issue 6 (23rd January 2014) - Galiana, Gigi; Peters, Dana; Tam, Leo; Constable, R. Todd
<x xml:space="preserve">Abstract</x> Purpose Nonlinear gradient encoding methods, such as O‐Space imaging, have been shown to provide good images from very few echoes. Acquiring data in a train of spin or gradient echoes is a very flexible way to further speed acquisition time. However, combining these strategies presents significant challenges, both in terms of the contrast and artifacts. We present strategies in both pulse sequence design and image processing to mitigate these effects. Theory and Methods The three strategies include a new echo ordering that takes into account the unique way that O‐Space samples the k‐space of the image; a new postprocessing filter that allows tuning of T2‐weighting by emphasizing the contribution of low frequency spatial information at selectable points in space and time; and an offset between linear and nonlinear gradients that makes the central point of each echo unique. Results Simulations indicate that these strategies mitigate artifacts introduced by T2 (or T2*) decay and produce contrast that reflects relaxation at a given echo time. Conclusion Turbo spin echo O‐Space is theoretically feasible, and the greater undersampling should make it possible to use shorter echo trains for a given scan time. Magn Reson Med 72:1648–1657, 2014. © 2014 Wiley Periodicals, Inc.